PERAN SOCIAL MEDIA SPECIALIST DAN CREATIVE STAFF DALAM KAMPANYE KOMUNIKASI PEMASARAN DEBIURYN DERMACOSMETICS SEBAGAI PENGUATAN BRAND POSITIONING PADA KALANGAN REMAJA PRIA DAN WANITA USIA 12–19 TAHUN DI KOTA SEMARANG - Greta Gabrielle Carl; Djoko Setyabudi (Interaksi Online, 2026)
The rapid expansion of the skincare industry has intensified market competition, requiring brands to implement more strategic and effective communication approaches. DeBiuryn Cosmetics faces challenges in the form of low brand awareness (14.6%) and suboptimal product sales among teenage consumers in Semarang. This study aims to examine the implementation of the integrated marketing communication campaign “Stay Bright, Stay Youth” in strengthening brand positioning and enhancing consumer engagement through both digital and offline channels. The campaign adopts an Integrated Marketing Communication (IMC) framework by combining digital activation on social media platforms, particularly Instagram and TikTok, with experiential marketing initiatives such as DeBiuryn Class Out. The findings indicate a significant improvement in digital performance, with Instagram followers increasing by 24% (from 485 to 600) and TikTok followers rising from 69 to 85. Furthermore, audience engagement grew by approximately 20%, as reflected in the increased number of views, likes, and comments across both platforms. In addition, brand awareness increased substantially from 14.6% to 84.8%, accompanied by product sales that exceeded the initial targets. These findings demonstrate that an integrated communication strategy, supported by effective social media management, plays a critical role in enhancing brand visibility, strengthening brand positioning, and driving consumer engagement among teenage audiences.